DESIGN CHARTS FOR MACHINE FOUNDATIONS (Journal of Engineering, 2007)
The problems of design of machine foundations for the special case of vertical mode of vibrationfor block foundation are presented in this paper. The empirical design method is used to get theresults using a computer program MATHCAD dealing with the parameters related to the machine.Design charts that are prepared to be a guide for the designer engineer are drawn. The design chartsare based on the variables limitations including the properties of the soil, machine and foundation.The design charts are based on three displacements which are acceptable for design of the machinefoundation.